Immune-Mediated Thrombotic Thrombocytopenic Purpura Following mRNA-Based COVID-19 Vaccine BNT162b2: Case Report and Mini-Review of the Literature - Buetler, Vanessa Alexandra; Agbariah, Nada; Schild, Deborah Pia; Liechti, Fabian D.; Wieland, Anna; Andina, Nicola; Hammann, Felix; Kremer Hovinga, Johanna A. (Frontiers in Medicine, 2022)
Introduction An increasing number of case reports have associated vaccinations against coronavirus disease 2019 (COVID-19) with immune-mediated thrombotic thrombocytopenic purpura (iTTP), a very rare but potentially life-threatening thrombotic microangiopathy, which leads to ischemic organ dysfunction. Thrombus formation in iTTP is related to a severe deficiency of the specific von Willebrand-factor-cleaving protease ADAMTS13 due to ADAMTS13 autoantibodies. Methods We present a case of iTTP following exposure to the mRNA-based COVID-19 vaccine BNT162b2 (Comirnaty®, Pfizer-BioNTech). In addition, we review previously reported cases in the literature and assess current evidence. Results Apart from our case, twenty cases of iTTP occurring after COVID-19 vaccination had been published until the end of November 2021. There were 11 male and 10 female cases; their median age at diagnosis was 50 years (range 14–84 years). Five patients (24%) had a preexisting history of iTTP. Recombinant adenoviral vector-based vaccines were involved in 19%, mRNA-based vaccines in 81%. The median onset of symptoms after vaccination was 12 days (range 5–37), with 20 cases presenting within 30 days. Treatment included therapeutic plasma exchange in all patients. Additional rituximab, caplacizumab, or both these treatments were given in 43% (9/21), 14% (3/21), and 24% (5/21) of cases, respectively. One patient died, despite a prolonged clinical course in one patient, all surviving patients were in clinical remission at the end of the observational period. Conclusion Clinical features of iTTP following COVID-19 vaccination were in line with those of pre-pandemic iTTP. When timely initiated, an excellent response to standard treatment was seen in all cases. ADAMTS13 activity should be determined pre-vaccination in patients with a history of a previous iTTP episode. None of the reported cases met the WHO criteria for assessing an adverse event following immunization (AEFI) as a consistent causal association to immunization. Further surveillance of safety data and additional case-based assessment are needed.